Post-stroke dysphagia: A review and design considerations for future trials - David Cohen; Christine Roffe; J. Beavan; B. Blackett; Carol Fairfield; Shaheen Hamdy; Diane Havard; Mary McFarlane; Carolee McLauglin; Marc Randall; Katie Robson; Polly Scutt; et al. (2016)
Post-stroke dysphagia (a difficulty in swallowing after a stroke) is a common and expensive complication of acute stroke and is associated with increased mortality, morbidity, and institutionalization due in part to aspiration, pneumonia, and malnutrition. Although most patients recover swallowing spontaneously, a significant minority still have dysphagia at six months. Although multiple advances have been made in the hyperacute treatment of stroke and secondary prevention, the management of dysphagia post-stroke remains a neglected area of research, and its optimal management, including diagnosis, investigation and treatment, have still to be defined.